The Existence Condition Of Environment And Disaster Literacy At Elementary School Student Mother In Bogor West Java - Bahagia Bahagia; Fachruddin Majeri Mangunjaya; Rimun Wibowo; Zulkifli Rangkuti (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to determine disaster education to increase environmental and disaster literacy, the role of the Disaster Agency in increasing knowledge about disasters. Another objective is to determine the behavior of student mothers in dealing with disasters through disaster literacy. The method used is qualitative with descriptive analysis. This method is applied because the research is related to the survey. Data collection was carried out through questionnaires, interviews, observation and documentation. Selection of informants using purposive sampling technique. The results are scrutinized through analysis of percentages. The results showed that the students' mothers were involved in disaster education so as to improve attitudes, knowledge and behavior. Another finding is that the students know about the role and function of disaster institutions to increase their literacy, usually information about disasters. Lastly, the behavior of the student's mother that has not been implemented properly, such as disaster risk reduction and environmental improvement of the house, includes not harvesting rainwater properly, less behavior in cultivating plants and fruit trees. At the same time, they have not created catchment areas for storing rainwater.Rsearch have contribution to goverment to create disaster literasy policy as well as the private sector which participate in disaster literacy